2021
DOI: 10.3389/fpsyg.2021.646435
|View full text |Cite
|
Sign up to set email alerts
|

From Resilience to Burnout in Healthcare Workers During the COVID-19 Emergency: The Role of the Ability to Tolerate Uncertainty

Abstract: The COVID-19 outbreak has placed extraordinary demands upon healthcare systems worldwide. Italy's hospitals have been among the most severely overwhelmed, and as a result, Italian healthcare workers' (HCWs) well-being has been at risk. The aim of this study is to explore the relationships between dimensions of burnout and various psychological features among Italian healthcare workers (HCWs) during the COVID-19 emergency. A group of 267 HCWs from a hospital in the Lazio Region completed self-administered quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
87
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 59 publications
14
87
0
4
Order By: Relevance
“…The third component of the MBI scale, Personal Accomplishment, detects no statistically significant difference on the average score ( p = 0.66). This data is in line with the available literature: Di Trani et al 45 found a higher level of MBI Personal Accomplishment in emergency professionals than in chronicity operators. In the same research, the “emergency group” expressed more feelings of competence, productivity, and successful achievement in one's work than the chronicity and service group.…”
Section: Discussionsupporting
confidence: 92%
“…The third component of the MBI scale, Personal Accomplishment, detects no statistically significant difference on the average score ( p = 0.66). This data is in line with the available literature: Di Trani et al 45 found a higher level of MBI Personal Accomplishment in emergency professionals than in chronicity operators. In the same research, the “emergency group” expressed more feelings of competence, productivity, and successful achievement in one's work than the chronicity and service group.…”
Section: Discussionsupporting
confidence: 92%
“…All pandemics, including the one caused by COVID-19, being unexpected and unpredictable events, which affect large numbers of people, are sources of stress (i.e., they are cataclysmic stressors, according to Lazarus and Cohen's definition [42]), and uncertainty among both ordinary people and HCWs [43][44][45]. If ordinary people experience "uncertainty about getting infected, uncertainty about the seriousness of the infection, uncertainty about whether the people around you are infected, uncertainty about whether objects or surfaces (e.g., money, doorknobs) are infected, uncertainty about the optimal type of treatment or protective measures, and uncertainty about whether a pandemic is truly over" [44] (p. 43), HCWs experience also other types of uncertainty (both professional and personal), that differ during the different stages of virus diffusion.…”
Section: Intolerance Of Uncertainty Personality and Copingmentioning
confidence: 99%
“…"Measures"). It can be considered as a sub-trait of anxiety [44] (that is, in its turn, a facet of neuroticism), which has often been found in association with stress, distress, insomnia, psychosomatic symptoms, and other clinical conditions in several recent studies carried out on COVID-19 among the general population and HCWs (e.g., [45,[51][52][53][54][55][56]). It is a cognitive, emotional, and behavioral tendency to react negatively to uncertain or ambiguous situations and unpredictable future events [57,58], which biases information processing, leading to faulty appraisals of threat, and reduces coping abilities [59].…”
Section: Intolerance Of Uncertainty Personality and Copingmentioning
confidence: 99%
“…According to MD Trani, 56% of HCWs in Italy showed EE Abbreviations: COVID-19, Novel coronavirus disease; HCW, Healthcare worker; MBI scale, Maslach Burnout Inventory scale; EE, emotional exhaustion; DP, depersonalization; PA, personal accomplishment; PPE, personal protective equipment; CR, composite reliability; AVE, average variance extracted. (Di Trani et al, 2021). In Portugal, Duarte I et al concluded that more than half of HCWs had symptoms of personal burnout (Duarte et al, 2020).…”
Section: Introductionmentioning
confidence: 99%